Feminism and Intersectionality in Academia Women's Narratives and Experiences in Higher Education (Springer International Publishing, 2018)
This edited volume explores the diversities and complexities of women's experiences in higher education. Its emphasis on personal narratives provides a forum for topics not typically found in in print, such as mental illness, marital difficulties, and gender identity. The intersectional narratives afford typically disenfranchised women opportunities to share experiences in ways that de-center standard academic writing, while simultaneously making these stories accessible to a range of readers, both inside and outside higher education.